Sleepiness and sleep quality in medical students of a Peruvian university - Rosales, Edmundo (2007)
Objective: To determine the degree of excessive daytime sleepiness and sleep quality in medical students. Design: Cross-sectional survey. Setting: Universidad Peruana Cayetano Heredia. Participants: Medical students. Interventions: No probabilistic sample of the sixth (76 externs) and seventh (74 interns) year medical students. Questionnaires: demographic data, Epworth sleepiness scale and Pittsburgh sleep quality index. Main outcome measures: Daytime sleepiness and sleep quality. Results: There was no difference in scores obtained between both populations. Of the participants, 58% had poor sleep quality and 34% had excessive daytime sleepiness. To have a subjective sleep latency more than 30 minutes, to sleep 6 hours or less, sleep efficiency less than 85% and to use hypnotic medication were related with poor sleep quality. Also, to sleep 5 hours or less, to consume caffeine and tobacco were related to poor sleep quality and excessive daytime sleepiness. The correlation between sleep quality and daytime sleepiness was R=0,426 p<0,001. Conclusions: We found a high frequency of poor sleep quality and excessive daytime sleepiness in medical students. These parameters were associated to caffeine and tobacco consume, long subjective sleep latency, short sleep duration, sleep efficiency less than 85% and use of hypnotic medication. Also we found correlation between sleep quality and daytime sleepiness.